Unmasking the Myth of Development in Imbolo Mbue’s How Beautiful We Were: A Postcolonial Ecocritical Analysis: Research article - Dhaba Dechasa, Rabbirra; Feleke Desta , Molla (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2024)
This study delves into Imbolo Mbue's literary masterpiece, How Beautiful We Were, to unravel the intricate themes of environmental exploitation, power dynamics, state vampirism, and the clash between nativist values and developmentalist pursuits. The purpose of this research was to analyze how the myth of development influences the interactions between different stakeholders and impacts the environment in the post-colonial context as reflected in this novel. The objectives of the study were to examine the perspectives of natives and developmentalists on land, explore power dynamics in the narrative, assess the effects of state vampirism on the ecosystem, and under-stand how the myth of development shapes environmental degradation. The method-ology employed was a qualitative approach grounded in postcolonial ecocritical theory, utilizing close reading and thematic analysis to unravel the complexities of the text. Drawing on theoretical analysis, the study uncovered the exploitative prac-tices of multinational corporations and governments, emphasizing the urgent need for sustainable practices and social justice. The findings revealed the destructive im-pact of unchecked industrial development on local communities and ecosystems, highlighting the complex relationship between development, environmental sustaina-bility, and social inequality. The implications of this research underscore the im-portance of reevaluating development paradigms to prioritize environmental protec-tion and community well-being in the postcolonial world. This study serves as a clar-ion call for equitable and sustainable development practices that honor the intercon-nectedness of humanity and the environment, paving the way for a more just and harmonious future.